A SAXS study of the pore structure evolution in biochar during gasification in H2O, CO2 and H2O/CO2. (15th May 2021) - Liu, Yurong; Paskevicius, Mark; Sofianos, M. Veronica; Parkinson, Gordon; Wang, Shuai; Li, Chun-Zhu
Graphical abstract: Highlights: Pore development in biochar gasified in H2 O/CO2 is similar to that in H2 O alone. Pore development is paralleled by the evolution of the aromatic structures. O-containing groups in biochar affect the final pore structure. Higher temperature gasification in H2 O and CO2 led to similar pore structures. Biomass particle size has little impact on the pore structure of biochar. Abstract: Gasification of biomass allows for its efficient utilisation as a renewable fuel through syngas production. This work presents the different effects of gasifying agents (H2 O, CO2 and H2 O/CO2 ) on the pore structure evolution in biochar during gasification. The effects of temperature (700, 800 and 900 °C) and biomass particle size (up to 5.6 mm) were also studied. The pore structure of biochar was characterized using synchrotron small angle X-ray scattering (SAXS). The pore development in biochar during gasification in H2 O/CO2 was close to that in H2 O. Carbon removal is more selective in CO2 than H2 O and the derived biochar displayed pore fractal features, whereas the biochars gasified in H2 O and H2 O/CO2 exhibited a surface fractal network due to the less selective carbon removal in the presence of H2 O. The pore structure development produced by various gasifying agents was paralleled by the evolution of the aromatic structures characterized by Raman spectroscopy. The different pore structure features result from the different reactivity of carbon sites with H2 O and CO2, which can be attributed to the different amounts of O-containing groups in biochar, as well as the different reactivity of H2 O and CO2 . Increasing temperature reduced the differences in pore structure between biochars gasified in H2 O and CO2 . Biomass particle size had little impact on the pore structure of biochar.